2012
DOI: 10.21836/pem20120503
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic examination of initial hoof contact, load distribution and break-over in the forelimbs of horses walking and trotting on a treadmill using the HoofTM System (Tekscan®)

Abstract: ZusammenfassungDie kinetische Bewegungsanalyse dient beim Pferd u.a. dazu, die Beurteilung von Hufkorrekturmaßnahmen mit technischen Mitteln zu verbessern. In der vorliegenden Arbeit wurde gezeigt, dass derartige Untersuchungen mit dem hier getesteten, relativ kostengünstigen Hoof TM -System (Tekscan ® ) zur Ermittlung der Druckverteilung unter der Hufsohle nicht nur wissenschaftlich, sondern auch unter Klinikbedingungen möglich sind. Außerdem wurde mit dieser Methode die Fußung, die Belastung und der Abrollvo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…However, in laminitic horses, relative vertical force and vertical impulse were higher in the heel region than in other regions, while in the control group, relative vertical force and vertical impulse were the highest in the toe region. These results agree with the findings in standing horses with severe laminitis, 8 which showed that the percentage of vertical force under the heel and toe was 61% and 39% respectively. Similarly, in obese ponies, which may be suffering from subclinical stages of laminitis, the load in the heel region was higher than that in the toe region 13 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, in laminitic horses, relative vertical force and vertical impulse were higher in the heel region than in other regions, while in the control group, relative vertical force and vertical impulse were the highest in the toe region. These results agree with the findings in standing horses with severe laminitis, 8 which showed that the percentage of vertical force under the heel and toe was 61% and 39% respectively. Similarly, in obese ponies, which may be suffering from subclinical stages of laminitis, the load in the heel region was higher than that in the toe region 13 .…”
Section: Discussionsupporting
confidence: 92%
“…This might explain the difference in the distribution pattern of forces in these two studies, as the gait can change the distribution of forces 14 . Our finding is in agreement with two previous studies that indicated greater load in the cranial half of the hoof while walking in unshod horses 8 and higher peak vertical force in the cranial half of the hoof than in the caudal half in sound shod horses 15 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It has frequently been used in equine research and was recommended for scientific and clinical application by Lange et al [17]. As some authors stated a lack of accuracy in using this piezoresistive foil sensors [19, 21, 31], most equine studies were confined to relative comparisons [14, 15, 17]. However, by use of an appropriate calibration under trial conditions and expected loads, an adequate accuracy could be obtained with this sensors [19–21].…”
Section: Discussionmentioning
confidence: 99%
“…Especially after proper calibration the piezoelectric sensors showed a reliable accuracy [20, 21]. The system was tested and recommended for scientific and clinical application by Lange et al [17]. …”
Section: Introductionmentioning
confidence: 99%